Nutrient intake and eating habits of triathletes on a Brazilian diet - Nogueira, J. A. D.; da Costa, T. H. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2004)
The objectives of this study were to determine the dietary habits, energy balance, and macro- and micronutrient dietary adequacy of triathletes, and to provide an athletes` food pyramid. Thirty-eight Brazilian triathletes, had anthropometric measurements taken. Mean (± standard deviation) body weight, height, and percentage body fat were 71.2 kg (± 9.4), 176.7 cm (± 5.5), and 12.3% (± 3.6) for men and 55.8 kg (± 5.2), 161.6 cm (± 4.5), and 24.3% (± 4.2) for women, respectively. A 24-h recall and a food-frequency questionnaire showed that mean total intakes of energy (MJ), carbohydrate, protein, and fat (g · kg-1 · d-1) were, respectively, 15.4, 7.3, 2.0, and 1.6 for men and 9.9, 5.9, 1.6, and 1.3 for women. The number of meals and intake of some food groups were insufficient, resulting in inadequate intake of carbohydrate and some micronutrients. Based on this study, athletes need help to achieve their sports-related nutrition goals, especially during intense training.